(untitled) (Bangladesh Journal of Public Administration, 2021)
The current crisis in Myanmar concerning the Rohingya people has resulted in a huge number of stateless refugees. An answer to the citizenship of these refugees is urgently required. This study summarizes the comparative analysis of the existing citizenship framework of Myanmar with the older version. After briefly reviewing earlier legal framework Citizenship Law of the Union 1948 concomitant to the 1947 Constitution of Burma, the study analyzes the changes made in Citizenship Law of Burma 1982 concomitant to the 1974 Constitution. Major results from the empirical studies conducted earlier suggest that there exist three types of citizenship in Myanmar while this study has found that there are four types of citizenship prevails in Myanmar. The study also has come out with the finding that there exists very little scope for Myanmar government to legalize a large number of Rohingya populations unless the Law is revised first. Therefore, the government should focus on the revision of the law if it really wants to prove its good intention for a sustainable solution.